2017
DOI: 10.3389/fnbeh.2017.00186
|View full text |Cite
|
Sign up to set email alerts
|

Different Molecular/Behavioral Endophenotypes in C57BL/6J Mice Predict the Impact of OX1 Receptor Blockade on Binge-Like Ethanol Intake

Abstract: Ethanol (EtOH) research has focused on stages of dependence. It is of paramount importance to more deeply understand the neurobehavioral factors promoting increased risk for EtOH binge drinking during the early stages of the addiction cycle. The first objective of this study was to evaluate whether C57BL/6J mice showing high drinking in the dark (DID) exhibit neurobehavioral traits known to contribute to EtOH binge-drinking disorders. Comparing high vs. low drinkers (HD/LD), we evaluated different types of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 66 publications
(98 reference statements)
3
21
0
Order By: Relevance
“…Previous studies using systemic Ox1R inhibition have suggested that Ox1Rs promote intake in higher-drinking individuals (Moorman and Aston-Jones, 2009; Alcaraz-Iborra et al, 2017; Moorman et al, 2017). We previously demonstrated that Shell Ox1Rs promote 2bc-DID drinking (Lei et al, 2016b) (see section “Materials and Methods”), and that animals drinking under this model reach binge-level blood alcohol concentrations (Lei et al, 2016a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using systemic Ox1R inhibition have suggested that Ox1Rs promote intake in higher-drinking individuals (Moorman and Aston-Jones, 2009; Alcaraz-Iborra et al, 2017; Moorman et al, 2017). We previously demonstrated that Shell Ox1Rs promote 2bc-DID drinking (Lei et al, 2016b) (see section “Materials and Methods”), and that animals drinking under this model reach binge-level blood alcohol concentrations (Lei et al, 2016a).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, some studies using systemic Ox1R inhibition have suggested that Ox1Rs are particularly important for promoting alcohol intake in higher-drinking individuals (Moorman and Aston-Jones, 2009; Alcaraz-Iborra et al, 2017; Moorman et al, 2017). However, the brain circuit in which Ox1Rs act to drive consumption in higher drinkers remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The DID procedure is a mouse model that triggers excessive binge-like EtOH drinking that was originally developed by Rhodes et al ( 2005 ) to generate high levels of voluntary EtOH consumption over a short period of time (2–4 h; Thiele and Navarro, 2014 ). The iDID is a prolonged and intermittent version of the standard DID (Alcaraz-Iborra et al, 2017 ). Thus, in the present study, iDID started at PND67 and continued for a total of eight, 7-day cycles, until PND120.…”
Section: Methodsmentioning
confidence: 99%
“…After every individual trial, the floor and walls of the apparatus were extensively cleaned with soapy water and totally dried with paper towels. Percentage of total number of entries to open arms and percentage of total time spent in open arms were registered for anxiety-like behavior assessment (Hargreaves and McGregor, 2007 ; Walf and Frye, 2007 ; Alcaraz-Iborra et al, 2017 ; Marianno et al, 2017 ). The total number of arm entries were recorded to assess locomotor activity (Hargreaves and McGregor, 2007 ; Alcaraz-Iborra et al, 2017 ; Marianno et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, drug and ethanol (EtOH) addiction research is dominated by studies addressing post-dependent stages of the addiction cycle, modeled by drug/EtOH dependence (Yardley and Ray, 2016 ; Spanagel, 2017 ) and drug/EtOH relapse preclinical procedures (Marchant et al, 2013 ; Vengeliene et al, 2014 ). Because continued binge-like consumption represents a risk behavior that favors transition to addiction (Koob and Le Moal, 2006 ; Courtney and Polich, 2009 ; Crabbe et al, 2011 ; Thiele and Navarro, 2014 ), we have alternatively focused our interest during the last years in the early pre-dependent stage of the addiction cycle dominated by repetitive binge-like intake (Alcaraz-Iborra et al, 2014 , 2017 ; Alcaraz-Iborra and Cubero, 2015 ; Carvajal et al, 2015 ; Rodríguez-Ortega et al, 2018 ). It is our, and others authors (Thiele and Navarro, 2014 ) believe, that understanding those neurobehavioral processes involved in repetitive binge consumption in non-dependent animals would help us to develop new approaches preventing transition to dependence.…”
Section: Introductionmentioning
confidence: 99%